Mentors' practice: the role of learning theory: an illuminative study - Rice, Rosalind (2008)
The initial focus of this thesis is on mentors' professional knowledge base, and subsequently on the pedagogical strategies employed by mentors and their use, in so far as it occurs, of adult learning theories, which have been said to form the dominant conceptual framework for mentoring (Hansford et al., 2003: 10). These issues are considered important as, despite acknowledgement by the DfES in 2001 as to the relevance of theory in mentor training, in practice mentor training is often limited to familiarisation with government and Partnership requirements in order for them to undertake the assessment of student teachers. Consequently very little attention is given to learning theories within mentor training. Whilst connections between mentoring and learning theories exist in literature my research highlights that there is a potential dichotomy between the literature and practice of mentoring. It therefore considers the extent to which adult learning theories are actually used in current mentoring practice. In addition my research also looks at the way mentor teachers' pedagogic strategies are shaped by the context and purposes they are working within, and the role ascribed to them. My research is based upon an in depth Case Study of 20 mentors from one HEI Partnership. It utilises qualitative method tools, with the primary tools being observations and semi-structured interviews. These tools assisted in progressively developing my research questions and conclusions as part of an inductive process. The results of my study show that the practice of mentors is largely influenced by their prior experience, primarily as teachers but also as student teachers; they see theory as having little influence on their practice. In addition my study indicates that few mentors are aware of learning theories or their principles. Nonetheless it indicates that the practice of most mentors includes the application of the principles of a number of adult learning theories. My research concludes that mentors use some of these principles through the development of their own personal construct theories, which in turn largely relies upon their prior experience, and through the framework provided by the HEI Partnership.